EXPORT PROMOTION POLICY AND ITS IMPACT ON ASEAN ECONOMIC DEVELOPMENT : A COMPARATION ANALYSIS ON INDONESIA AS ASEAN COUNTRIES - Adany, Daneta Fildza (Jurnal Ilmiah Mahasiswa FEB, 2017)
The main objective of this research is to analyze whether international trade policies that lead to exports promotion would benefit ASEAN economic development. The study used secondary data in the 1993 to 2013 in five countries of ASEAN, namely Indonesia, Malaysia, Philippines, Thailand and Singapore. 3SLS methods is used to estimate the impact of export promotion policies on economic development, which is indicated by: (i) the growth of agricultural sector, (ii) the growth of industrial sector, (iii) the growth of exports, and (iv) the growth of GDP. The estimation results indicate that the reduction in the import tariff that reflects the higher degree of export promotion policy turned out to encourage the acceleration of industrialization based on agriculture, so as to encourage the export of agro-industry commodities and accelerate the economic growth. In addition, the estimation results also suggest that increased degree of export promotion could have a negative impact on economic growth, if industrialization had weak linkages with the agricultural sector.Keywords : International trade, export promotion, import tariff, industrialization